2012
DOI: 10.1021/ef300612z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Naphthenic Acids onto Mineral Surfaces Studied by Quartz Crystal Microbalance with Dissipation Monitoring (QCM-D)

Abstract: In the present research, the adsorption of naphthenic acids from n-dodecane solutions onto hydrophilic surfaces of the most common minerals in petroleum reservoirs (silica, alumina, and calcite) has been investigated using the quartz crystal microbalance with dissipation monitoring (QCM-D). The wettability and surface roughness of the mineral surfaces applied for the QCM-D measurements were determined with contact angle and atomic force microscopy (AFM) measurements. Corrections for changes in bulk density and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 49 publications
(68 reference statements)
2
20
0
1
Order By: Relevance
“…This conclusion is consistent with available literature. [24][25][26][27][28][29][30] Agreement with the Langmuir equilibrium model in Figure 7 is incompatible because of the observed irreversible attachment of toluene-solubilized asphaltene to the silica surface. However, slow rearrangement kinetics of initially reversible adsorbed configurations can lead to an early-time apparent Langmuir isotherm.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This conclusion is consistent with available literature. [24][25][26][27][28][29][30] Agreement with the Langmuir equilibrium model in Figure 7 is incompatible because of the observed irreversible attachment of toluene-solubilized asphaltene to the silica surface. However, slow rearrangement kinetics of initially reversible adsorbed configurations can lead to an early-time apparent Langmuir isotherm.…”
Section: Resultsmentioning
confidence: 91%
“…Our measured amounts are in general agreement with literature despite differences in asphaltene sources. [24][25][26][27][28][29] Asphaltene strongly adsorbs from toluene onto silica when not in the presence of water.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to asphaltenes, naphthenic acids are of lower molecular weight, typically less than 450 g/mol, spanning mainly C 10 to C 50 compounds with up to six fused ring structures that are mostly saturated [35]. Naphthenic acids preferentially adsorb on carbonate solid surfaces mainly by chemical interactions to modify the wettability from water-wet to oil-wet as the surface becomes saturated, although the process is reversible at elevated temperatures [36,37].…”
Section: Dynamics Of Oil Film Recessionmentioning
confidence: 99%
“…Highly polar components such as carboxyli et al showed that naphthenic acids readily adsorb and are retained by calcite, even after a desorption sequence. 5 Molecular dynamics simulations (MD) revealed that alcohols can adsorb strongly to the calcite surface, effectively altering its wettability. 6 Gomari and Hamouda concluded that medium chain fatty acids are able to alter the wettability of calcite, even when a thin water film is present.…”
Section: Introductionmentioning
confidence: 99%